Photon diagnostics at the FLASH THz beamline. (10th May 2019) - Pan, Rui; Zapolnova, Ekaterina; Golz, Torsten; Krmpot, Aleksandar J.; Rabasovic, Mihailo D.; Petrovic, Jovana; Asgekar, Vivek; Faatz, Bart; Tavella, Franz; Perucchi, Andrea; Kovalev, Sergey; Green, Bertram; et al.
Abstract : A range of THz diagnostic tools developed for THz/XUV pump–probe experiments at FLASH1, DESY, are presented. Abstract : The THz beamline at FLASH, DESY, provides both tunable (1–300 THz) narrow‐bandwidth (∼10%) and broad‐bandwidth intense (up to 150 uJ) THz pulses delivered in 1 MHz bursts and naturally synchronized with free‐electron laser X‐ray pulses. Combination of these pulses, along with the auxiliary NIR and VIS ultrashort lasers, supports a plethora of dynamic investigations in physics, material science and biology. The unique features of the FLASH THz pulses and the accelerator source, however, bring along a set of challenges in the diagnostics of their key parameters: pulse energy, spectral, temporal and spatial profiles. Here, these challenges are discussed and the pulse diagnostic tools developed at FLASH are presented. In particular, a radiometric power measurement is presented that enables the derivation of the average pulse energy within a pulse burst across the spectral range, jitter‐corrected electro‐optical sampling for the full spectro‐temporal pulse characterization, spatial beam profiling along the beam transport line and at the sample, and a lamellar grating based Fourier transform infrared spectrometer for the on‐line assessment of the average THz pulse spectra. Corresponding measurement results provide a comprehensive insight into the THz beamline capabilities.